2018
DOI: 10.1007/s10577-018-9579-y
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal distribution of soybean retrotransposon SORE-1 suggests its recent preferential insertion into euchromatic regions

Abstract: Retrotransposons constitute a large portion of plant genomes. The chromosomal distribution of a wide variety of retrotransposons has been analyzed using genome sequencing data in several plants, but the evolutionary profile of transposition has been characterized for a limited number of retrotransposon families. Here, we characterized 96 elements of the SORE-1 family of soybean retrotransposons using genome sequencing data. Insertion time of each SORE-1 element into the genome was estimated on the basis of seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…It is worth noting that three families of Copia elements were under positive selection (adaptive molecular evolution) pressure (Figure 7A), and insertion position structure analysis results indicated that these elements integrated mainly within the promoter or gene regions (Figure 8B,C, Figures S7 and S8), introducing some cis -acting regulatory elements to the promotors of genes (Table S1) or playing import roles in the evolution of some genes. As reported in previous studies, Gypsy elements tend to be clustered into the chromosomal centromeric regions [11,17,34], while other studies suggested that Copia elements were largely within and/or close to gene regions [35,36,37]. These results suggested that, of the two-retrotransposon superfamilies, the Copia elements may have the dominant influence on the evolution of some mulberry genes.…”
Section: Discussionsupporting
confidence: 62%
“…It is worth noting that three families of Copia elements were under positive selection (adaptive molecular evolution) pressure (Figure 7A), and insertion position structure analysis results indicated that these elements integrated mainly within the promoter or gene regions (Figure 8B,C, Figures S7 and S8), introducing some cis -acting regulatory elements to the promotors of genes (Table S1) or playing import roles in the evolution of some genes. As reported in previous studies, Gypsy elements tend to be clustered into the chromosomal centromeric regions [11,17,34], while other studies suggested that Copia elements were largely within and/or close to gene regions [35,36,37]. These results suggested that, of the two-retrotransposon superfamilies, the Copia elements may have the dominant influence on the evolution of some mulberry genes.…”
Section: Discussionsupporting
confidence: 62%
“…Similar phenomena had also been found in soybean [ Glycine max (L.) Merr. ], in which Copia ‐type retrotransposon ( SORE‐1 ) insertions are more recently and frequent in chromosome arms than in pericentromeric regions (Nakashima et al, 2018). A typical example is that it inserted in the first intron of the GmFT2a gene of soybean where it attenuated the expression level of this gene, causing delays in flowering (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the "copy and paste" mechanism underlying the amplification of LTR retrotransposons, they have been shown to make up the largest classes of transposable element (TE) content in the genomes of most flowering plants, greatly contributing to increases in size of their host genome [66]. As reported in studies concerning Arabidopsis, soybean, and flax genomes, Copia elements are largely located within and/or close to gene-coding regions, which suggests that these elements may have the dominant influence on the evolution of some gene families [67][68][69]. Gene prediction revealed features characteristic of gene-rich regions, with an average of 13 coding sequences per 100 Mbp for both GS and PEPC gene regions ( Table 1, Supplementary file 1).…”
Section: Narrow-leafed Lupin Gs and Pepc Are Encoded By Multigene Fammentioning
confidence: 99%